1985
DOI: 10.1111/j.1365-2559.1985.tb02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell dysplasia and hepatocellular carcinoma: a histoiogical and immunohistochemical study

Abstract: Liver cell dysplasia (LCD) was found in 28 (60%) of 47 patients with hepatocellular carcinoma (HCC); 22 (79%) of them had associated liver cirrhosis. LCD was more frequently observed in posthepatitic cirrhosis (82%) than in the other forms. Carcinoembryonic antigen (CEA), alpha-1-antitrypsin (AAT) and alpha-fetoprotein (AFP), as demonstrated by the peroxidase-antiperoxidase method, were similarly expressed both in normal and in dysplastic cells. Hepatitis B surface antigen was found in eight cases (17%), six o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…We identified two cases of metastatic adenocarcinoma containing small numbers of cells positive for aFP and it is clear that this antibody is not entirely specific for HCC. A further point of interest was the consistent positive staining of non-neoplastic hepatocytes for aFP, similar to the findings in previous studies 1,21 . However, other authors have found aFP positivity to be confined to HCC with no staining of benign liver cell neoplasms or of non-neoplastic hepatocytes 8 .…”
Section: Discussionsupporting
confidence: 82%
“…We identified two cases of metastatic adenocarcinoma containing small numbers of cells positive for aFP and it is clear that this antibody is not entirely specific for HCC. A further point of interest was the consistent positive staining of non-neoplastic hepatocytes for aFP, similar to the findings in previous studies 1,21 . However, other authors have found aFP positivity to be confined to HCC with no staining of benign liver cell neoplasms or of non-neoplastic hepatocytes 8 .…”
Section: Discussionsupporting
confidence: 82%
“…Nonneoplastic control cases displayed uniformly diploid stemlines whereas hepatocellular carcinomas had in 8/ I0 cases bimodal or trimodal populations. Thus, LCD is a heterogeneous lesion in terms of ploidy, and the abnormal DNA content observed in some cases supports its pre-neoplastic nature.Liver-cell dysplasia (LCD) is a morphological alteration of hepatocytes (Anthony et al, 1973).Its pre-neoplastic significance has been inferred in several reports because of its frequent association with hepatocellular carcinoma (HCC) and/or chronic hepatitis B virus infection (Bartok et al, 1981; Ho et al, 1981;Akagi et al, 1984;Roncalli et al, 1985Roncalli et al, , 1986. We have observed some morphometric similarities between LCD and HCC (Roncalli et al, 1988).…”
mentioning
confidence: 60%
“…This agreement among separate among studies. 23,[26][27][28][29][30] One recent report has proposed that studies using different methodologies and patient popula-LCC represents a response to prolonged cholestasis. 31 tions strongly suggests that the two lesions are linked in To help untangle this controversy, we assessed the prog-some underlying pathogenetic fashion and argues against nostic value of LCC for HCC through a matched case-control LCC representing merely a degenerative or regenerative alterstudy that compared the occurrence of LCC between cir-ation.…”
Section: Discussionmentioning
confidence: 99%